Photosystem II Photochemistry and Phycobiliprotein of the Red Algae Kappaphycus alvarezii and Their Implications for Light Adaptation. (27th November 2013) - Guan, Xiangyu; Wang, Jinfeng; Zhu, Jianyi; Yao, Chunyan; Liu, Jianguo; Qin, Song; Jiang, Peng
Abstract : Photosystem II photochemistry and phycobiliprotein (PBP) genes of red algae Kappaphycus alvarezii, raw material of κ -carrageenan used in food and pharmaceutical industries, were analyzed in this study. Minimum saturating irradiance (I k ) of this algal species was less than 115  μ mol m −2  s −1 . Its actual PSII efficiency (yield II) increased when light intensity enhanced and decreased when light intensity reached 200  μ mol m −2  s −1 . Under dim light, yield II declined at first and then increased on the fourth day. Under high light, yield II retained a stable value. These results indicate that K. alvarezii is a low-light-adapted species but possesses regulative mechanisms in response to both excessive and deficient light. Based on the PBP gene sequences, K. alvarezii, together with other red algae, assembled faster and showed a closer relationship with LL- Prochlorococcus compared to HL- Prochlorococcus . Many amino acid loci in PBP sequences of K. alvarezii were conserved with those of LL- Prochlorococcus . However, loci conserved with HL- Prochlorococcus but divergent with LL- Prochlorococcus were also found. The diversities of PE and PC are proposed to have played some roles during the algal evolution and divergence of light adaption.